2002
DOI: 10.1007/s003440010041
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoskeleton and Gravitropism in Higher Plants

Abstract: The cellular and molecular mechanisms underlying the gravitropic response of plants have continued to elude plant biologists despite more than a century of research. Lately there has been increased attention on the role of the cytoskeleton in plant gravitropism, but several controversies and major gaps in our understanding of cytoskeletal involvement in gravitropism remain. A major question in the study of plant gravitropism is how the cytoskeleton mediates early sensing and signal transduction events in plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 0 publications
2
78
0
4
Order By: Relevance
“…The direct involvement of the cytoskeleton and the vacuole in the gravitropic response has also been recently documented (Blancaflor, 2002;Kato et al, 2002b). A small number of proteins potentially involved in anchoring the vacuole to the cytoskeleton were identified.…”
Section: Cytoskeletonmentioning
confidence: 85%
“…The direct involvement of the cytoskeleton and the vacuole in the gravitropic response has also been recently documented (Blancaflor, 2002;Kato et al, 2002b). A small number of proteins potentially involved in anchoring the vacuole to the cytoskeleton were identified.…”
Section: Cytoskeletonmentioning
confidence: 85%
“…Changes in auxin, ethylene, gravity signaling, or alteration in cell wall properties alter hypocotyl growth direction (De Grauwe et al, 2005;Vandenbussche et al, 2011). The cytoskeleton also plays a crucial role in optimal hypocotyl direction as evident by the hypocotyl phenotypes of seedlings harboring mutations in genes encoding various microtubule-interacting proteins (Blancaflor, 2002;Bisgrove, 2008). Exogenous BR application or enhanced endogenous BR signaling compromised the ability of dark-grown seedlings to penetrate a hard medium.…”
Section: The Relevance Of Br For Optimal Hypocotyl Growth Directionmentioning
confidence: 99%
“…Findings from the actin disruption experiment suggest that the saltatory movement of amyloplasts through transvacuolar strands is dependent upon the actin cytoskeleton. The actin cytoskeleton has been proposed as a major player in plant gravitropism (Yoder et al, 2001;Blancaflor, 2002;Hou et al, 2003). Recent studies, however, showed that an intact actin cytoskeleton is not required for gravity perception in inflorescence stems and roots (Yamamoto and Kiss, 2002;Hou et al, 2003) and likely acts to downregulate gravitropism by continuously resetting the gravitropic-signaling system (Hou et al, 2004).…”
Section: Amyloplast Movement For Gravity Perception Is Likely To Be Amentioning
confidence: 99%